The Development, Transformation, and Use of The Children's Language - Henny Dewi Koeswanti (Universitas Pendidikan Ganesha, 2021)
There are still many children who have difficulty learning foreign languages. In addition, children also have difficulty in memorizing foreign language vocabulary. Language development for children has a dynamic nature because many factors can influence it. This study aims to identify various forms of language development and transformation experienced by students and students of TPA. This type of research is qualitative research. The research method used in this study is a case study on the development, transformation, and use of language by children who are members of TPA students. This case study was conducted to identify the phenomenology of dynamic use and development of children's language through the TPA program. Data were collected through observation and interviews. The data analysis technique is descriptive qualitative analysis. The study results indicate that there is a development, transformation, and use of a unique and exciting language that is influenced by the context of TPA as the realm of informal education based on Islamic education. This is evident from the various forms of language used by children who experience vocabulary development until they are transformed into code-switching and Arabic code-mixing. The use of Arabic can be seen as an opportunity because it can increase children's knowledge and vocabulary, but at the same time, it can also be seen as a threat to the survival of the mother tongue and national language for children.